Rare contacts between synapses and microglial processes containing high levels of Iba1 and actin – a postembedding immunogold study in the healthy rat brain. Issue 1 (17th April 2013) - Sogn, Carl J. L.; Puchades, Maja; Gundersen, Vidar
Abstract Although microglia is recognised as the cell‐mediating innate immunity in the brain, emerging evidence suggests a role of microglia in synaptic communication and modulation. The ability of microglia to move in the neuropil and contact synapses is crucial for such a function. However, the frequency of microglial contact with synapses is not known. Microglia motility is regulated by actin polymerisation and its interaction with ionising calcium‐binding adaptor protein 1 (Iba1). In order to move and make contact with synapses, delicate microglial processes should contain high levels of actin and Iba1. To study this we refined an electron microscopic postembedding immunogold method enabling us to identify and quantitatively study different microglial constituents in intact brain tissue. We show that Iba1 and actin were colocalised at high densities in delicate processes in the rat frontal cortex, and that these delicate processes of microglia contact synaptic elements. About 3.5% of the synapses received direct contact from microglia. There was a marked inverse correlation between the densities of Iba1/actin gold particles and the area of the microglial processes, suggesting that the most delicate processes possess the machinery to provide movement in the neuropil. The low frequency of microglia interaction with synaptic elements suggests that microglia have a limited role in overall regulation of synaptic activity.